Hungarian Monitoring, 18 January 1989 . [Magyar rádiófigyelő], 1989. január 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - American foreign minister criticizes Israel for its continued territorial occupation policy - International reactions to the Vienna conference - Reform wing of the Polish parliament accepts decision concerning legal pluralism of parliament - French head of state begins Bulgarian visit - More demonstrations in Prague Domestic Affairs: - Parliamentary Cultural Committee in session - Pause in cultural relations with Romania - National minorities - Is there a legal basis for the Workers' Militia? - Plan package for location of possible Budapest World Exposition Economy: - Manager of the year is Sándor Demján, former director of Hungarian Credit Bank - Internal struggle and harmony of farm structures: the government is ready to abolish factors that block progress in agriculture Külpolitika: - Az amerikai külügyminisztérium bírálta Izraelt a megszállt területeken folytatott politikája miatt - Külföldi visszhangok a bécsi konferenciához - A Lengyel parlament reformszárnya elfogadta a parlamenti törvény pluralizmusról szóló határozatát - A francia államfő megkezdte bulgáriai látogatását - Újabb tüntetések Prágában Belpolitika: - Ülésezik az Országgyűlés Kulturális Bizottsága - Romániával a kulturális kapcsolat szünetel - Nemzeti kisebbségek ügye - Van-e jogi alapja a munkásőrségnek - Csomagterv készül az esetleges budapesti világkiállítás tervezett színhelyéről Gazdaság: - Az év menedzsere Demján Sándor, a Magyar Hitelbank vezérigazgatója - A gazdálkodási formák belső harca és harmóniája - A kormányzat kész arra, hogy a fejlődést gátló tényezőket felszámolja a mezőgazdaságban